Development of a water resource allocation model based on the dynamic exploitable amount of groundwater and its application in the Jinghe County, Xinjiang - Lu, Yao; Ma, Zhenzhen; Wang, Ting; Xie, Xinmin; Gu, Yanling (Frontiers in Environmental Science, 2022)
The exploitable amount of groundwater in arid regions is related to changes in water resources utilization patterns, and the traditional water resources allocation model assumes a constant exploitable amount of groundwater. In this study, a water resources allocation model consisting of a water resources optimal allocation module, an exploitable amount analysis module, and a mutual feedback iterative module connecting the above two modules, is established based on the dynamic exploitable amount of groundwater. The proposed model is applied to Jinghe County, Xinjiang, which is one of the most arid regions in the world. The results show that the actual exploitable amount of groundwater in 2035 will be 181.54 million m³ when changes in the exploitable amount of groundwater in response to changes in the water resources utilization patterns are considered, which is 43.99 million m³ lower than the current amount, and the groundwater supply will be 167.82 million m³. However, the groundwater supply based on the current exploitable amount of groundwater (225.53 million m3) will be 188.29 million m3, which is 6.75 million m3 higher than the actual exploitable amount of groundwater and thus may lead to groundwater overdraft. This is mainly attributed to the reduction in the exploitable amount of groundwater with the reduction in farmland, and it is estimated that the exploitable amount of groundwater would be decreased by about 110,000 m3 with the reduction of 1 km2 farmland. The results of this study underline the need to consider changes in the exploitable amount of groundwater in the allocation and management of water resources in arid regions, and the model developed in this paper can provide an effective tool for rational allocation of water resources in arid regions.